K Korelasi antar Dukungan Keluarga, Efikasi Diri dan Kepatuhan Hemodialisa pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Era Widia Sary (Journal of Nursing Invention, 2022)
Background: Chronic kidney failure is one of the main health problems in the world, where this disease can completely stop kidney function. Apart from transplantation, the only treatment that can be done is hemodialysis therapy to help the patient survive. Patient compliance in undergoing therapy is an important thing to note, otherwise this can worsen his health condition. Factors that strengthen individuals to comply in undergoing hemodialysis are support that comes from the closest people such as family and from within oneself (self-efficacy). Objective: This study aims to determine the correlation between family support, self-efficacy and hemodialysis compliance in chronic renal failure patients undergoing hemodialysis at Banjarmasin Islamic Hospital. Method: This type of quantitative research uses a correlational research design with a sample of 25 respondents. Collecting data using a questionnaire sheet and analyzed using the spearman rank statistical test. Result: Based on the results of the analysis, the correlation between family support and self-efficacy obtained p-value = 0.002 which means there is a significant correlation between family support and self-efficacy, correlation analysis between family support and hemodialysis compliance is obtained p-value = 0.000. Conclusion: There is a significant correlation between family support and self-efficacy in chronic renal failure patients  hemodialysis.